Die Millenniums-Runde der WTO-Verhandlungen und die Zukunft der EU-Agrarpolitik; The millennium round of WTO negotiations and the future of EU agricultural policy - Stefan Tangermann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– The Uruguay Round has established completely new rules for agricultural trade, but not yet achieved much liberalisation. The current new round of negotiations will, therefore, have to make another big step forward. Countries' views on what exactly should be agreed in the new round still differ widely. However, it is remarkable that no country has so far doubted the validity of the new WTO rules for agriculture, nor refused to engage in serious negotiations about further reductions. The EU has so far not had major difficulties to honour the new commitments that resulted from the Uruguay Round, though in the area of export subsidies the constraints have already been felt. In the new round of negotiations, EU export subsidies will be a primary target of negotiations, given the fact that the EU grants around 88 % of all agricultural export subsidies world-wide. It will, therefore, be important for the EU to change its policies such that EU agriculture can export without subsidies. In the cereals sector, Agenda 2000 has made a notable step in this direction. For other products, though, the EU will need more reforms in the future.
Keywords: 330; Internationale Handelspolitik; EU-Agrarpolitik; EU-Staaten; Welt